IMPLEMENTASI GREEN MARKETING PADA PELAKU UMKM KAIN SASIRANGAN: TELAAH PEMASARAN ISLAMI - Annisa Mahfuzah (Program Studi Ekonomi Syariah IAI Darul Ulum Kandangan, 2023)
The consumer trend to use environmentally friendly products is increasing. This movement is known as “green consumerism or green awareness”. Sasirangan cloth is one of the products that is expected to support green awareness. Entrepreneurs have many challenges to realize the green concept as a whole in their business. Banjarmasin is known as the City of a Thousand because the river has become the lifeblood of the Banjar people. So it is important that the quality of the river is also a concern. Through this paper, it can be seen the implementation of green marketing that can be carried out by MSME players by outlining the initiatives of Islamic marketing approaches. This study uses qualitative research methods by understanding the phenomenon of green awareness and analyzing the overall actions of MSME actors in making Sasirangan cloth. In the processing of Sasirangan Fabric there is a process that produces waste. There are still many Sasirangan cloth MSME actors who dispose of the liquid waste directly into the river without filtering which can cause pollution and decrease in water quality. This is against the concept of Islamic marketing. To start green marketing, Sasirangan Fabric MSME actors can adopt an environmentally friendly Islamic marketing concept. The management of liquid waste from the processing of Sasirangan cloth can be part of the production cost. Another alternative, what can be done by SMEs Sasirangan Fabric in implementing green marketing, namely in the production process using natural dyes that are more friendly to the environment.